THE EFFECT OF THE THINK TALK WRITE TYPE COLLABORATIVE LEARNING MODEL ON THE OUTCOMES OF LEARNING TO WRITE POETRY IN GRADE VII STUDENTS OF SMP SASTA GKPS 3 PEMATANGSIANTAR - Erri Kisando Sinaga; Mulyono (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine whether there is a significant influence in learning to write poetry on seventh grade students of GKPS 3 Pematangsiantar Private Middle School. This study was conducted in 2025 at GKPS 3 Pematangsiantar Private Middle School. This study is a quantitative study with an experimental approach and uses a one group pretest-posttest model. Furthermore, this study will be compared with related test samples at a significant level or a level of 0.05 (95%). The result is the average pretest value = 43.5 and the average posttest value = 76.5. From the data analysis, the research hypothesis was tested using the "t" test. From the results of the study, t count = 31.41 was obtained with a significant level of 0.05 (95% confidence level) with df 20 obtained t table 3.16. thus if t count > t table namely (31.14>3.16) then Ho is rejected, with the rejection of Ho then Ha is accepted. It can be concluded that the results of the poetry writing ability of class VII students of GKPS 3 Pematangsiantar Private Middle School are better after using the Cooperative Learning Think Talk Write learning model.